DETERMINAN ALIRAN FOREIGN DIRECT INVESTMENT DI INDONESIA (PENDEKATAN MODEL DUNNING) - Claudia TeziaJanuarita Putri; Regina Niken Wilantari (MediaTrend, 2016)
Traffic capital across countries is one of  investment opportunities from domestic and abroad to stimulate the economic growth  of developing countries. Compared to other forms of capital, Foreign Direct Investment is the flow of capital is long-term and relatively not as vulnerable to economic shocks. The aim of this study is to see the performance of FDI movement as a capital inflow in Indonesia and to explores whether factors that affect FDI using Dunning’s ecletic model. This study focused on two basic analysis, descriptive analysis and quantitative analysis using the Error Correction Model (ECM). The results of short-term ECM estimate shows that FDI is influenced by inflation and the degree of economic openness. Furthermore, the result in the long term ECM estimate show that only variable that infrastructure does not significantly affect the movement of FDI in Indonesia.